2021
DOI: 10.1126/sciadv.abf8653
|View full text |Cite
|
Sign up to set email alerts
|

Multistep mechanism of G-quadruplex resolution during DNA replication

Abstract: G-quadruplex (or G4) structures form in guanine-rich DNA sequences and threaten genome stability when not properly resolved. G4 unwinding occurs during S phase via an unknown mechanism. Using Xenopus egg extracts, we define a three-step G4 unwinding mechanism that acts during DNA replication. First, the replicative helicase composed of Cdc45, MCM2-7 and GINS (CMG) stalls at a leading strand G4 structure. Second, the DEAH-box helicase 36 (DHX36) mediates bypass of the CMG past the intact G4 structure, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 81 publications
4
30
0
Order By: Relevance
“…In the lagging strand, G4s do not stall replicative helicases but their formation still requires resolution. PIF1 ( Dahan et al, 2018 ), and FANCJ ( Sato et al, 2021 ) were reported to unfold lagging strand G4s. During telomere dsDNA replication, WRN was found to unfold G4s in lagging strand ( Crabbe et al, 2004 ).…”
Section: G-quadruplex Unwinding Helicases and Their Functionsmentioning
confidence: 99%
“…In the lagging strand, G4s do not stall replicative helicases but their formation still requires resolution. PIF1 ( Dahan et al, 2018 ), and FANCJ ( Sato et al, 2021 ) were reported to unfold lagging strand G4s. During telomere dsDNA replication, WRN was found to unfold G4s in lagging strand ( Crabbe et al, 2004 ).…”
Section: G-quadruplex Unwinding Helicases and Their Functionsmentioning
confidence: 99%
“…Experiments with Polδ were performed in 25 mM TRIS-HCl pH 7.5, 150 mM NaCl, 8 mM MgCl 2 , 1 mM TCEP, 1 mM ATP and 0.2 mg/ml BSA. We used single stranded plasmid DNA as template for DNA synthesis, and it was produced as previously described(63). The concentrations reported here are for the final reaction that contains all components.…”
Section: Methodsmentioning
confidence: 99%
“…In mammalian cells, BLM helicase activity has been shown to resolve G4s and disrupt steric impediments during replication preventing genome instability, as BLM gene depletion resulted in increased levels of stabilized G4s and telomere fragility in murine fibroblasts [ 70 ]. A coordinated action of three helicases, DHX35, FANCJ and the replicative CMG complex, has recently been shown to promote bypass and unfolding of stabilized G4s during replication in an ex-vivo model of Xenopus egg extracts [ 77 ]. Mammalian telomeres are also recognized by the ssDNA-binding complex CST (CTC1-STN1-TEN1), which can target and unwind G4s in vitro.…”
Section: Main Textmentioning
confidence: 99%